2011
DOI: 10.1186/1471-2164-12-126
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the human pathogen Acinetobacter baumannii under iron limiting conditions

Abstract: BackgroundIron acquisition systems are important virulence factors in pathogenic bacteria. To identify these systems in Acinetobacter baumannii, the transcriptomic response of the completely sequenced strain ATCC 17978 under iron limiting conditions was investigated using a genomic microarray that contained probes for all annotated open reading frames.ResultsUnder low iron conditions, transcription levels were more than 2-fold up-regulated for 463 genes, including 95 genes that were up-regulated more than 4-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
262
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(275 citation statements)
references
References 64 publications
(81 reference statements)
11
262
2
Order By: Relevance
“…The BLAST algorithm identified two uncharacterized open reading frames (ORFs), A1S_0474 and A1S_0980 (ATCC 17978 numbering), as the closest hits, sharing amino acid identities of 44% with PiuA and 51% with PirA of P. aeruginosa, respectively. Both genes have been shown to be preceded by putative Fur binding sites (A1S_0474, GCGAATAATAATAATTCTTATTTAT, and A1S_0980, GATATTGTTAATAATTATC ATTATT) (33), suggesting regulation by iron availability via the Fur iron uptake regulator. Downstream of the piuA gene of A. baumannii, we identified an ORF (A1S_0473) showing 52% amino acid identity with piuC from P. aeruginosa and ybiX from Escherichia coli (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BLAST algorithm identified two uncharacterized open reading frames (ORFs), A1S_0474 and A1S_0980 (ATCC 17978 numbering), as the closest hits, sharing amino acid identities of 44% with PiuA and 51% with PirA of P. aeruginosa, respectively. Both genes have been shown to be preceded by putative Fur binding sites (A1S_0474, GCGAATAATAATAATTCTTATTTAT, and A1S_0980, GATATTGTTAATAATTATC ATTATT) (33), suggesting regulation by iron availability via the Fur iron uptake regulator. Downstream of the piuA gene of A. baumannii, we identified an ORF (A1S_0473) showing 52% amino acid identity with piuC from P. aeruginosa and ybiX from Escherichia coli (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2). A transcriptome analysis performed in A. baumannii strain ATCC 17978 recently showed that expression of both piuA and pirA is induced under iron-limiting conditions (33). A. baumannii strains harbor at least three distinct siderophore clusters, one of them being the acinetobactin biosynthesis operon.…”
Section: Discussionmentioning
confidence: 99%
“…A custom-designed 8× 15,000 spot Agilent microarray for A. baumannii ATCC 17978 described was used (28). cDNA synthesis, labeling, and hybridizations were conducted at the Ramaciotti Centre for Gene Function Analysis, Australia, as described (28). Statistical analyses were performed by using the SAM algorithms (29), and all results reported were found to be significant by using a false discovery rate of 5%.…”
Section: Methodsmentioning
confidence: 99%
“…A custom-designed 8× 15,000 spot Agilent microarray for A. baumannii ATCC 17978 described was used (28). cDNA synthesis, labeling, and hybridizations were conducted at the Ramaciotti Centre for Gene Function Analysis, Australia, as described (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation